MANAJEMEN PAI BERBASIS INKLUSI DI SEKOLAH MENENGAH PERTAMA - Farida (Al Ulya: Jurnal Pendidikan Islam, 2021)
The purpose of this study was to find out: 1) learning planning for ABK 2) organizing learning for ABK 3) learning implementation for ABK, and 4) learning evaluation for ABK. The results of this qualitative research found several things, namely 1) Learning planning for Children with Special Needs. First, it starts with first determining the criteria for normal students and children with special needs, followed by identifying and establishing the management of inclusive classes. Second, identify and map. Third, develop a Learning Implementation Plan with an inclusive education model. 2) Organizing learning with the inclusive education model, is done by adjusting the time allocation for subject matter. 3) The implementation of learning with the inclusive education model is carried out using a scientific approach with five scientific activities, namely: observing, asking, reasoning, trying, and creating networks. While the learning model applied by the teacher includes: inquiry learning, discovery learning and project-based learning methods which are collaborated with lecture methods, habituation, question and answer, assignments and collaborated with singing and cooperative among students classically. 4) Evaluation of learning with the inclusive education model uses authentic assessment, namely: performance assessment, project assessment, portfolio assessment, written assessment.